DIAGNOSTIC SYSTEMS FOR EARLY DETECTION OF DISEASES - Abdukadirov Nuriddin (Western European Studies, 2025)
The integration of modern technology into healthcare has revolutionized the early detection of diseases, improving patient outcomes and reducing healthcare costs. This article explores diagnostic systems that leverage artificial intelligence, machine learning, the Internet of Things (IoT), and big data analytics to enhance early disease detection. The study highlights various applications, including cancer detection, cardiovascular disease prediction, diabetes management, and neurological disorder diagnosis. Challenges and future prospects of these technologies are also discussed, providing insights into the role of innovative diagnostic systems in modern medicine.
Keywords: Diagnostic systems; early disease detection; artificial intelligence